2004
DOI: 10.1161/01.atv.0000120376.09047.fe
|View full text |Cite
|
Sign up to set email alerts
|

Expansive Arterial Remodeling: Location, Location, Location

Abstract: Abstract-The artery is a dynamic organ capable of changing its geometry in response to atherosclerotic plaque formation.Expansion of the vessel diameter retards luminal narrowing and is considered a compensatory response. However, the expansive remodeling response is a "wolf in sheep's clothes," because expansion is associated with the presence of inflammatory cells, proteolysis, and a thrombotic plaque phenotype. The prevalence and clinical presentation of expansively remodeled lesions may differ among vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 90 publications
3
88
0
7
Order By: Relevance
“…Most of the concepts of arterial remodeling are based on histological studies (one time point data) of coronary arteries (2,16,17). Therefore, little is known about the change of arterial wall dimensions in the carotid artery over time.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the concepts of arterial remodeling are based on histological studies (one time point data) of coronary arteries (2,16,17). Therefore, little is known about the change of arterial wall dimensions in the carotid artery over time.…”
Section: Discussionmentioning
confidence: 99%
“…EDA in the plaque may activate Tlr4 and initiate an inflammatory response, like a fraction of EDA is able to activate Tlr4 and initiate an inflammatory cascade [14]. But Tlr4 activation is also important for collagen turnover [20] and VSMC proliferation [30]. EDA might trigger SMC proliferation via Tlr4 activation, leading to stabilization and reorganization of the plaque, which results in conversion of an unstable inflammatory plaque into a stable, smooth muscle cell rich plaque.…”
Section: Local Eda Levels In the Plaquementioning
confidence: 99%
“…Recently, we and others showed that Tlr4 activation accelerates arterial occlusion by neointima formation, plaque formation, geometrical remodeling and plaque destabilization [18][19][20][21]. It remains unclear which ligands activate Tlr4 and thereby promote atherosclerotic luminal narrowing.…”
Section: Introductionmentioning
confidence: 99%
“…20 Plaque with expansive remodeling has been shown to have a significantly larger lipid core and higher macrophage count than negatively or less positively remodeled plaque. 31 Recent studies have also shown that expansive carotid remodeling was associated with low endothelial stress and plaque rupture 4,5 and was significantly greater in patients with cerebral ischemic symptoms than in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%